Regulation of Early Light-Inducible Protein Gene Expression by Blue and Red Light in Etiolated Seedlings Involves Nuclear and Plastid Factors. - Adamska, I. (1995)
Early light-inducible proteins (ELIPs) are nuclear-encoded chloroplast proteins whose genes are transiently transcribed during the greening process of etiolated plants. In the present work the regulation of ELIP gene expression by blue and red light has been investigated in plumulas of etiolated pea plants (Pisum sativum). The results show that the steady-state level of ELIP transcripts is controlled by a combined action of phytochrome and blue light receptor systems and, in addition, depends on the age of the seedlings. Both a low-light fluence system of blue and a very-low-fluence system of red light are involved in ELIP induction. The threshold for accumulation of ELIP transcripts was as low as 10-5 [mu]E m-2 s-1 for both light qualities but a different pattern of accumulation was obtained in blue and in red light. Blue light not only acts at the level of transcription but also regulates the stability of the ELIP transcripts in a light intensity-dependent manner. Moreover, it is shown that product(s) of nuclear gene(s) negatively regulate the steady-state level of ELIP transcripts during the 1st h of illumination with red light. Preillumination of seedlings with white light abolishes this repression. Accumulation of ELIP transcripts requires "plastid factors" in both blue and red light qualities.